Direct determination of phosphite in fertilizers by flow-injection amperometry - Franzini, Vanessa Pezza; Fugivara, Cecilio Sadao [UNESP]; Benedetti, Assis Vicente [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Cavalheiro, Eder Tadeu Gomes; Gomes Neto, José Anchieta [UNESP] (Wiley-Blackwell, 2007)
A sensor based on graphite electrode modified with palladium-platinum-palladium film is proposed for phosphite determination by flow-injection amperometry. The modified electrode was prepared by a sequential cathodic deposition of Pd, Pt and Pd on a graphite electrode from 0.5% m/v PdCl2 + 28% m/v NH4OH and 2% m/v H2PtCl6 + 10% v/v H2SO4 solutions. After suitable conditioning, the electrode showed catalytic activity for phosphite oxidation when 0. 15 V was applied. The proposed system handles approximately 50 samples per hour (0.0.1 - 0.05 mol L-1 Na-2 HPO3; R-2 = 0.9997), consuming ca. 70 mu L of sample per determination. The limit of detection and amperometric sensibility were 5 X 10(-4) mol L-1 and 1.5 mA L mol(-1), respectively. The proposed method was applied to analysis of fertilizer samples without pre-treatment. Results are in agreement with those obtained by spectrophotometry and titrimetry at 95% confidence level and good recoveries (96-109%) of spiked samples were found. Relative standard deviation (n=12) of a 0.01 mol L-1 Na2HPO3 sample was 2%. The useful lifetime of modified electrode was around 220 determinations. For routine purposes it means that this electrode can be continuously used for 5 hours.
Keywords: phosphite; fertilizer; modified electrode; flow-injection analysis